Acute corneal toxicity of latanoprost with different preservatives. (2nd April 2016) - Uematsu, Masafumi; Mohamed, Yasser Helmy; Onizuka, Naoko; Ueki, Ryotaro; Inoue, Daisuke; Fujikawa, Azusa; Sasaki, Hitoshi; Kitaoka, Takashi
Abstract: Purpose : To investigate the corneal toxicity of Xalatan and three latanoprost generics using transepithelial electrical resistance (TER) and scanning electron microscopy (SEM). Methods : Corneal TER changes after a 60-s exposure to Xalatan (latanoprost 0.005% preserved with 0.02% BAC), and latanoprost generics (Latanoprost PF BAC free, Latanoprost Nitten SB containing sodium benzoate and Latanoprost Towa containing 0.01% BAC with sodium chloride polysorbate 80 as additive) were measured in living rabbits. Corneal damage was also examined by SEM. Hank's balanced salt solution (HBSS) was used as a control. Results : There was a significant decrease in the corneal TER after exposure of the cornea to Xalatan ( p < 0.01) and all latanoprost generics ( p < 0.01: Latanoprost PF, p < 0.05: Latanoprost Nitten SB, Latanoprost Towa) as compared to HBSS. All latanoprost generics showed less TER decrease in the corneal TER as compared to Xalatan ( p < 0.01). SEM revealed that superficial cells of Xalatan-treated corneas were damaged and exhibited degenerated microvilli. Conversely, the superficial cells of corneas exposed to HBSS or all latanoprost generics appeared normal and had normal microvilli under SEM examinations. Conclusion : The corneal toxicity of Xalatan is greater than that of latanoprost generics. Xalatan contains 0.02% BAC, which may be responsible for the corneal toxicity.